Transformation of Human Resource Management in Education in the Era of Technological Disruption: A Systematic Literature Review - Elfrianto, Elfrianto (Lembaga Riset Mutiara Akbar, 2023)
This study aims to analyze the transformation of educational human resource management in the era of technological disruption through a systematic literature review of nine scientific articles published between 2018 and 2023. The review identifies trends, strategies, and challenges faced by educational institutions in implementing digital-based human resource management. The findings reveal that digital transformation not only affects administrative systems but also reshapes leadership paradigms and organizational culture within education. Educational leaders play a strategic role in fostering innovation and collaboration through visionary and adaptive digital leadership. Moreover, the application of human resource analytics (HRA) has emerged as a new approach for data-driven decision-making in teacher development and performance evaluation. This study concludes that the success of educational human resource transformation depends on the synergy between technology, leadership, and a continuous learning culture aimed at improving human quality and institutional effectiveness.